Intramedullary schwannoma of cervicomedullary junction: A case report - Tahta, Alican; Çetinkal, Ahmet; Çakır, Aslı; Şekerci, Zeki (Elsevier Masson s.r.l., 2022)
Background: Intramedullary schwannomas of brain stem and spinal cord are extremely rare. In almost all cases, homogeneous, asymmetrical or circular intensive gadolinium enhancement has been demonstrated. However, no cases reported previously with minimal contrast enhancement in cervicomedullary junction. Case description: A 38-year old man presented with a one-month history of constant, radiative right shoulder and arm pain. There was no pathological finding in his neurological examination. Also, physical evidence or family history of neurofibromatosis was not found. Magnetic resonance imaging of brain and cervical spine showed intramedullary, solid-cystic lesion localized in the cervicomedullary junction with unobvious gadolinium enhancement. The mass was gross totally resected through a sub-occipital craniotomy via midline approach. Postoperative pathological examination confirmed diagnosis of schwannoma. No changes were detected in the neurological examination of the patient after the operation. Conclusions: There are 3 previously reported intramedullary schwannomas of the cervicomedullary junction in the literature. To the best of our knowledge, this is the first case of unobvious contrast enhancing intramedullary schwannoma of the cervicomedullary junction. The possibility of schwannoma should not be excluded when a mass with slight contrast enhancement is detected in the intramedullary region of the cervicomedullary junction.
Keywords: Cervicomedullary Junction; Intramedullary; Schwannoma; Surgical Treatment